COMMUNITY GOVERNANCE FOR POVERTY ALLEVIATION - Sudarmo Sudarmo (Yustisia, 2016)
AbstractThe Al-Munawaroh Muslim is an Islamic communitygrowing in Gilingan urban area of Surakarta City. Most members of this association and many people living around the area were living in poverty. This situation was perceived as a common problem and challenge for the community to resolve it. The aim of this study is to discuss critically the contemporary evident on community governance in Surakarta in line with the Indonesian Constitution of 1945, the Law 13/2011, and the Presidential Decree 166/2014 and that of 96/2015. One case study of the religion-based association namely the Al Munawaroh Muslim of Surakarta has been examined with regard to the networks created by the community in delivering community governance. By using ethnographic method, this research showed that the community had capacity to govern common problem despite its limited capacity; it has capacity to provide sustainable public service for the poor because its leaders, advisers and experienced members were together able to create social capital including internal networks among its members and external networks with other institutions horizontally and vertically. Conflict of some officials of the community was unavoidable because of different interests and preferences among them in managing the resource they belong, and some membersof the communitywere to be self-interest resulting in distrust among the majority of the members to them. Although the community had a capacity of governance by providing public service for the poor with food material and financial assistances, it was not a substitution but a complement for the state role in alleviating poverty.